Environmental Sustainability Preparing for Tomorrow - Abdul Rehman Khan, Syed (IntechOpen, 2021)
This book examines the global challenges of air pollution and its consequences at domestic and international levels. Industrialization and logistical operations are the critical factors of carbon emissions, damaging fauna and flora. In addition, air pollution adversely affects human health. As such, this book discusses possible solutions to mitigate air pollution both domestically and internationally.